AI-Powered Data Integration in Multi-Cloud Environments: Bridging the Gap with Intelligent Automation - Prakash Reddy Vanga (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative role of AI-powered data integration in multi-cloud environments, addressing the growing challenges organizations face in managing distributed cloud infrastructures. As enterprises increasingly adopt multi-cloud strategies, these businesses encounter significant challenges in data integration, security, and operational efficiency. The article examines how artificial intelligence and machine learning technologies are revolutionizing cloud integration through automated data mapping, intelligent data movement, and enhanced governance capabilities. It analyzes the implementation of centralized monitoring systems and advanced analytics capabilities that enable organizations to maintain comprehensive visibility across their cloud environments. Through an examination of current market trends and future developments, the article demonstrates how AI-driven solutions are enabling organizations to overcome integration complexities while ensuring data security and compliance. The article also provides a framework for implementing these solutions, including best practices for assessment, platform selection, and deployment optimization, while considering emerging trends such as autonomous operations, edge computing integration, and blockchain-based data integrity solutions.